Effect of exposure to formalin on peripheral and smaller airways of 1st-year medical students - Dipak Kumar Dhar (Wolters Kluwer Medknow Publications, 2020)
Context: One of the occupational hazards experienced by a doctor is the exposure to formaldehyde during gross anatomy dissection classes. As it vaporizes at room temperature, the respiratory system is easily affected. The present study was conducted to assess the effect of formaldehyde on the smaller and peripheral airways. Aims: The study aimed to evaluate the effect of formaldehyde exposure on the smaller and peripheral airways of 1st-year medical students. Settings and Design: A longitudinal, descriptive study was conducted in the Department of Physiology, Rohilkhand Medical College and Hospital, among 1st-year MBBS students in the academic year 2015-16. Materials and Methods: The spirometric parameter, forced expiratory flow at 25%-75% (FEF25%-75%)was recorded in eighty medical students using spirometer RMS Helios 401 available in the research laboratory of the department. Percent-predicated values were used for the analysis. The baseline values were recorded at the beginning of the academic calendar and followed up at the end of the 1st, 6th, and 10th months. Statistical Analysis Used: Data were analyzed using the SPSS software. Descriptive statistics and repeated measures ANOVA were used for the analysis.P <0.05 was considered statistically significant. Results: The overall mean FEF25%-75%declined up to the 6th month following which there was a gradual correction. The overall pattern of change and the decrease in 1st month was statistically significant (P = 0.001). Conclusions: There is some detrimental effect of formaldehyde on smaller and peripheral airways which affects the ventilatory dynamics.